IC 9409 The Materials Flow Of Vanadium In The United States - Henry E. Hilliard (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The production, use, and emission of vanadium in the United States has been traced for the year 1991. Consumption was 3,300 tons2, exports 1,285 tons, and imports 2,013 tons. About 98% of production was used in metallurgy; the remainder was consumed in chemicals, including catalysts. Total emissions to the environment in 1991 were estimated at about 3,100 tons, including emissions due to the combustion of coal and petroleum products. Emissions resulting from the production of ferrovanadium were 130 tons, and emissions from the production of steel about 6 tons. Dissipative losses, defined as losses that occurred during use or as a result of wear, were estimated to be no more than 3 tons. Disposal losses were estimated to be about 4,600 tons. Most of these losses were steel products that contained 0.1% or less vanadium and mayor may not have been recycled. When these products are recycled by the steel industry, vanadium ends up in the steelmaking slag and does not return to vanadium use cycle. Worldwide emissions due to anthropogenic and natural sources were briefly reviewed. It was concluded that industrial emissions were about three times greater than emissions from natural sources.